Effect of Zeolite Nano-Materials and Artichoke (Cynara scolymus L.) Leaf Extract on Increase in Urinary Clearance of Systematically Absorbed Nicotine - Malekshah, R. E.; Mahjub, R.; Rastgarpanah, M.; Ghorbani, M.; Partoazar, A. R.; Mehr, S. E.; Dehpour, A. R.; Dorkoosh, F. A. (Arzneimittelforschung, 2012)
Nicotine, the main pharmacologically active component in tobacco and cigarette, has some toxic effects and also high potential for addiction. In this study, the effect of artichoke (Cynara scolymus L.) and zeolite nano-materials on urinary excretion of nicotine and consequently elimination of systematically absorbed nicotine was investigated. A simple, valid and highly sensitive high performance liquid chromatography method has been developed for determination of nicotine in rat urine according to guidelines for bioanalysis.It was found that nano-zeolites can cause increase in urinary concentration of nicotine due to its high surface adsorption. Artichoke leaf extract can cause increase in urinary excretion of nicotine in longer post administration times. It was observed that co-administration of nanozeolites and the leaf extract has the synergetic effect on increasing the urinary excretion of nicotine.
Keywords: nicotine; high performance liquid chromatography; artichoke leaf extracts (ALE); zeolite nano-materials